The Effect of Bleaching Clay on the Quality of Refined and Bleached Palm Oil - Chua, Hooi Ling (2001)
The aim of this study was to characterize the physicochemical properties of the bleaching clays used in the refining of palm oil. Acid-activated, neutral and natural clays as well as synthetic adsorbent were analysed by various techniques: scanning electron microscopy, thermal analysis (Differential Thermal Analysis and Thermogravimetric Analysis), X-ray diffraction (XRD), determination of surface area, pore-size and particle-size distribution. The effects of these physical and chemical properties of bleaching clays on the quality of refined palm oil were subsequently investigated. The XRD patterns showed that silica (quartz) was present in all of the analyzed commercial clays. The acid activated clays - Tonsil and WAC Omega consisted mainly of montmorillonite. The TGA, DTA and XRD results showed that the commercial clay - Pure Flo was essentially attapulgite type of clay. WAC Supreme, the acid activated clay, displayed a complicated XRD pattern indicating that besides tron magnesium aluminium silicate (montmorillonite), attapulgite and other impurities were present. The study on the effect of degumming acid on the quality of RBO oil indicated that increased concentration of phosphoric acid facilitated the removal of iron in the RBO oil. On the other hand, the copper content in the oil was likely to be influenced by the type of clay used in the bleaching process. Langmuir isotherm was more applicable than Freundlich isotherm in the adsorption of trace metals, copper and iron, from degummed palm oil on Pure Flo. The adsorption of phosphorus by Pure Flo, Attapulgite and WAC Supreme conformed to both Langmuir and Freundlich isotherms. On the other hand, adsorption of pigments, chlorophyll and carotene on the clay adsorbents fitted the Freundlich model better than the Langmuir model. The data showed that the acid activated clay of WAC Supreme with high surface area and large pore volume did not necessary possess better bleaching efficiency than Pure Flo and Attapulgite. Pure Flo is the best clay adsorbent compared to WAC Supreme and Attapulgite (Hudson Resource). The degummed-bleached palm oil after bleaching with Pure Flo showed the lowest concentration of phosphorus, copper, chlorophyll and carotene pigments. Conversely, WAC Supreme is a poor adsorbent of phosphorus, iron and secondary oxidation products. High concentrations of copper and carotene were retained in the degummed-bleached palm oil after bleaching with Attapulgite (Hudson Resource).